Effects of Solid-State Fermented (SSF) Pelleted Feed with Lactobacillus plantarum on Tachysurus fulvidraco: Growth, Digestion, Antioxidant, Immunity, Intestinal Morphology, and Microbiota - Tao Wang; Jianqiao Wang; Shasha Zhang; Junjie Xu; Xiaojing Dong; Shuyan Miao; Longsheng Sun (Fishes, 2023)
This study aimed to evaluate the effects of solid-state fermented commercial pelleted feed with Lactobacillus plantarum on growth performance, digestive physiology, antioxidant, and immune capacity, as well as morphology and microbiota in intestinal of Tachysurus fulvidraco. A total of 420 fish (49.96 ± 7.10 g) were randomly allocated to twelve 300 L buckets for a 60 d farming trial. The diets of three treatments were established: the untreated commercial diet (UCD), the commercial diet mixed with fermented liquid (MFLD), and the solid-state fermented commercial diet (SSFD). The results indicated that SSFD treatment had a significant positive effect on the growth performance of T. fulvidraco, with an increase of 15.69% to 16.57% (p